Oncologic outcomes of transoral robotic surgery for HPV‐negative oropharyngeal carcinomas. Issue 10 (8th June 2021) - Parhar, Harman S.; Weinstein, Gregory S.; O'Malley, Bert W.; Shimunov, David; Rassekh, Christopher H.; Chalian, Ara A.; Newman, Jason G.; Basu, Devraj; Cannady, Steven B.; Rajasekaran, Karthik; Lin, Alexander; Lukens, John N.; et al.
Abstract: Background: Patients with human papillomavirus (HPV)‐negative oropharyngeal squamous cell carcinoma (OPSCC) continue to experience disappointing outcomes following chemoradiotherapy (CRT) and appreciable morbidity following historical surgical approaches. We aimed to investigate the oncologic outcomes and perioperative morbidity of a transoral robotic surgery (TORS) approach to surgically resectable HPV‐negative OPSCC. Methods: Retrospective analysis HPV‐negative OPSCC patients who underwent TORS, neck dissection and pathology‐guided adjuvant therapy (2005–2017). Results: Fifty‐six patients (91.1% stage III/IV) were included. Three‐year overall survival, locoregional control, and disease‐free survival were 85.5%, 84.4%, and 73.6%, respectively (median follow‐up 30.6 months, interquartile range 18.4–66.6). Eighteen (32.1%) patients underwent adjuvant radiotherapy and 20 (39.3%) underwent adjuvant CRT. Perioperative mortality occurred in one (1.8%) patient and hemorrhage occurred in two (3.6%) patients. Long‐term gastrostomy and tracheostomy rates were 5.4% and 0.0%, respectively. Conclusion: The TORS approach for resectable HPV‐negative OPSCC can achieve encouraging oncologic outcomes with infrequent morbidity.